2019
DOI: 10.1161/atvbaha.118.311758
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of PAR4 (Protease-Activated Receptor 4)-Mediated Platelet Activation by a Synthetic Nonanticoagulant Heparin Analog

Abstract: Objective— PAR4 (protease-activated receptor 4), one of the thrombin receptors in human platelets, has emerged as a promising target for the treatment of arterial thrombotic disease. Previous studies implied that thrombin exosite II, known as a binding site for heparin, may be involved in thrombin-induced PAR4 activation. In the present study, a heparin octasaccharide analog containing the thrombin exosite II–binding domain of heparin was chemically synthesized and investigated for anti-PAR4 effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Similarly, another PAR1 antagonist inhibited nonocclusive thrombosis on collagen at 600 s −1 , although not at a higher shear of 1800 s −1 36 . Conversely, thrombosis over collagen was reduced by a PAR4 inhibitor 35 . Similarly, a PAR4‐blocking antibody inhibited platelet procoagulant activity under arterial shear over collagen and reduced fibrin formation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another PAR1 antagonist inhibited nonocclusive thrombosis on collagen at 600 s −1 , although not at a higher shear of 1800 s −1 36 . Conversely, thrombosis over collagen was reduced by a PAR4 inhibitor 35 . Similarly, a PAR4‐blocking antibody inhibited platelet procoagulant activity under arterial shear over collagen and reduced fibrin formation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…8,9,14,68,69 S ánchez Centellas et al 70 reported that an anionic cluster (Asp224, Asp230, Asp235) in ECL2 is important for PAR4 activation by thrombin, which agrees with a more complex model of PAR4 activation that has emerged with roles for the extracellular loops of the PAR4 and exosite II of thrombin. [70][71][72] Our model in which the N terminus is docked near the extracellular loops would facilitate these additional interactions between PAR4 and thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that heparin and other molecules interacting with exosite II inhibit platelet aggregation induced by γ-thrombin ( 10 ), a proteolytic degradation product of thrombin that lacks exosite I and solely retains the capacity to cleave PAR4. Moreover, a low molecular weight synthetic heparin analog specifically designed to target exosite II has been found to inhibit thrombin-induced PAR4 activation ( 16 ). For bivalirudin, the biphasic PAR signaling response observed herein can be linked to thrombin's gradual proteolytic cleavage of bivalirudin, as this process leaves both exosite II and the active site free to interact with PAR4 while preserving bivalirudin's blockage of exosite I, a domain that is particularly important for PAR1 activation ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…As exosites I and II have been shown to be crucial for determining thrombin substrate recognition (14,15), the differential engagement of these thrombin domains by heparin and bivalirudin could result in alterations in substrate specificity that might have consequences for the pharmacodynamic effects of these drugs. This concept is supported by the previous finding that a synthetic low molecular weight heparin analog without anticoagulant activity selectively inhibited PAR4-mediated platelet aggregation at low thrombin concentrations (16). The purpose of this study was to test the hypothesis that the different mechanisms employed by unfractionated heparin/antithrombin and bivalirudin to inhibit thrombin result in differential inhibition of thrombin-induced platelet activation responses via PAR1 and PAR4.…”
Section: Introductionmentioning
confidence: 88%